Tri Mandala in the Layout of Pakraman Penglipuran Bangli, Bali - Reandini Syu'ara Dewi; Ahadiat Joedawinata (ARTic, 2021)
Penglipuran Pakraman Village, located in the administrative village of Kubu, Bangli District, Bangli Regency, is one of the Pakraman villages in Bali Province. Penglipuran Pakraman Village maintains the traditions and traditional values of Balinese people in daily life based on Hindu teachings and also as a tourist village. The people of Penglipuran Pakraman Village carry out the philosophy of Tri Hita Karana in terms of their lives, one of which is applying the concept of Tri Mandala in the spatial layout of the village. This can be seen from the arrangement of houses, temples and other areas that produce a spatial layout that provides order, comfort and beauty. The purpose of this study is to determine the concept of Tri Mandala applied in Penglipuran village layout through literature study. Based on the literature study, the Tri Mandala concept is the concept of division of space and the value of the space area, the concept of traditional Balinese architecture, the concept of house layout, the concept of village layout, consisting of Nista Mandala, Madya Mandala and Utama Mandala. in the Nista Mandala area there is a village cemetery, Pura Dalem Pelapuhan, Pura Dalem Pingit, Bangli Regency hero's graveyard, sports field and agricultural area. In the Madya Mandala area there are Pakraman village settlements, banjar halls and sports fields, in the Main Mandala area there are Penataran Temples / Bale Agung Temples / Puseh Temples and bamboo forests. Keyword: Culture; Desa Pakraman; Penglipuran; Spatial planning; Tri Mandala